EPIDEMIOLOGICAL PROFILE OF NURSING STUDENTS AT A PUBLIC UNIVERSITY: A FOCUS ON MATERNITY - Rocha, Roseany Patrícia Silva; Campos, Ana Julia Mascarello Ferreira; da Silva, Eimillyn Nathalia Bessa Souza; Rocha, Rosemara Andressa da Silva; da Silva, Ronaldo Antonio; Mocheuti, Karina Nonato (Seven Editora, 2025)
Motherhood can generate great challenges for students in the health area, since the child requires affection, time, attention and care together with the extensive study routine and workload imposed by the training process. This study aimed to evaluate the epidemiological profile of nursing students along with the impact of motherhood on academic performance, and to analyze the main perceptions, motivations and challenges during academic training. This is a descriptive, cross-sectional study with a quantitative approach. It was possible to conclude that the students who are mothers have particular difficulties when experiencing motherhood and dealing with graduation, having limitations regarding the two workdays study/maternity. DOI: https://doi.org/10.56238/sevened2024.037-176